Genetic analysis of SLC47A1, SLC22A1, SLC22A2, ATM gene polymorphisms among diabetics in an Indian population - Phate, Sagar D.; Daswani, Bharti R.; Mishra, Deepika N.; Joshi, Kedar S. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Metformin is a first-line therapy for type 2 diabetes mellitus. However, the glycaemic response to metformin is likely to be affected by polymorphisms of transporter genes. Therefore, the study was done with the aim to assess demographic distribution of transporter genotypes involved in disposition and action of metformin. Methods: This cross-sectional, observational, single centre, clinical study was conducted in 80 diabetic patients recruited from medicine OPD. Descriptive analysis was done for distribution of the four transporter genotypes viz. SLC47A1 (rs2289669), ATM (rs11212617), SLC22A2 (rs316019) and SLC22A1 (rs622342). Genotyping was determined by DNA extraction, agarose gel electrophoresis, estimation of DNA concentration, polymerase chain reaction, DNA sequencing, sequencing analysis. Results: Transporter genotype analysis showed that for SLC47A1 (rs2289669) transporter, 31.25% and 26.25% were homozygous for AA and GG allele respectively, while 42.5% were heterozygous (AG). For ATM (rs11212617), SLC22A2 (rs316019) and SLC22A1 (rs622342) transporter, 45% and 10%, 1.25% and 80%, 58.75% and 7.50% were homozygous for AA and CC allele respectively; while 45%, 18.75%, 33.75% were heterozygous (AC) respectively. Interethnic differences in the genotype and allele frequencies of SLC22A1 (rs622342) and ATM (rs11212617) gene polymorphism were observed when compared with other major populations. Conclusions: In the genotypic distribution of four transporter genotype study showed that there was an ethnic variation in allelic distribution of allele A and C of ATM (rs11212617) and SLC22A1 (rs622342) while AA genotype of SLC22A2 (rs316019) was rare genotype and allele ‘A’ was major allele found in our study. The study data observed would justify further pharmacogenetic studies to evaluate the role of gene polymorphism in the therapeutic efficacy of metformin.